Microstructural features and mechanical properties of in-situ remelting welding of TC4 titanium alloy and T2 copper welded joint by electron beam - Jie Zhou; Shun Guo; Zehaochen Deng; Yong Peng; Qi Zhou; Huning Bi; Kailei Zhao; Hongyi Xu; Kehong Wang (Journal of Materials Research and Technology)
In order to achieve high-quality welding of titanium copper dissimilar metals, the in-situ remelting welded joints of TC4 and T2 were obtained by using a time-sharing dual electron beam(TDEB). A welded joint consisting of the IMCs layer, FZ zone, copper weld zone, and titanium side HAZ is formed in the TC4/T2 interface area. The microstructure and morphology of IMCs layers in welded joints with TDEB welding and copper offset welding were observed by using SEM and TEM. Multiple forms of IMCs were observed in the IMCs layer, including columnar Ti2Cu, granular Ti3Cu4, and sheet-like TiCu4, clarifying the orientation relationship between some precipitates and matrix phases. The TC4/T2 joint welded with TDEB welding achieved micro zone remelting of the IMCs layer. The thickness of the IMCs layer has significantly decreased, and the number of copper-rich phases in the IMCs layer has increased, which improves the mechanical properties of the welded joint. The TC4/T2 joint welded by time-sharing dual beam electron beam has a tensile strength of 215.9 MPa and an elongation of 6.14%. The joint exhibits brittle quasi dissociation fracture. The main factor causing fracture is the high brittleness and hardness of titanium-rich phases such as TiCu and Ti2Cu. This study provide a new welding method for titanium copper dissimilar metals, as well as research ideas for dissimilar metal welding.